Study Of Changes In The Manggar Baru Coastline Using Numerical Methods - Danduru, Jeaneth Bintang; Wahab, Muhammad Fajrin; Fauzi, Ardiyanzyah; Sukmara, Riyan Benny; Wirawan, Muhammad Khaisar (Naval Architecture Department, Kalimantan Institut of Technology, 2024)
Coastline's change was caused by the movement of sediments influenced by waves, wind, and materials around the shore. The movement of sediments around the coast resulted coastal dynamics marked by abrasion and Erosion. In the Balikpapan region, especially on the East Balikpapan Coast near the Makassar Strait, causing high waves on the beaches in this area, one of the areas that was once affected was Manggar Baru Beach, where there was a settlement less than 10 meters from the shoreline. With the changes in the coastline, it could lead to floods, changes in the area, damage to facilities around the coast, and so on. This study is modeled with the help of an application to understand the characteristics of the coastline to get trends in the present and projected future changes for disaster mitigation. It was also found that the average changes in 2024 were 0.829 m/year, in 2027 were 1.984 m/year, in 2032 were 3.982 m/year, and in 2042 were 7.689 m/year. Changes that occurred in Manggar Baru Beach were predominantly experiencing Erosion every year.